Emerging Technologies and Marketing Strategy: A Bibliometric Review of Digital Marketing and Innovation - Legito, Legito; Eva Andriani (Eastasouth Institute, 2023)
The landscape of marketing strategies is undergoing a profound transformation fueled by the rapid emergence of technologies. This study employs a comprehensive bibliometric analysis to explore the dynamic relationship between emerging technologies, marketing strategies, digital marketing, and innovation. Through co-citation analysis, bibliographic coupling, keyword co-occurrence analysis, and VOSviewer visualizations, the research objectives are achieved, unraveling trends, influential authors, institutions, and research themes within the multidimensional field. Findings underscore the multidisciplinary nature of the domain, highlighting clusters ranging from customer satisfaction and digital platforms to market orientation and social media marketing. Prominent keywords like